AUTENTIKASI ISRĀILIYYĀT DALAM TAFSIR AL-QUR’AN - Rohmah, Khoirida; Mildasari, Dina Aulia (AL ITQAN: Jurnal Studi Al-Qur'an, 2022)
The background of this research is respond to israiliyyat as one of the instruments in interpreting the Qur'an. On the other hand, without us realizing it, the presence of israiliyyat might represent a threat to the religion, hence this subject of israiliyyat must be thoroughly researched  so as not to cause misunderstandings in understanding the Qur'an. This study focuses on what and how israiliyyat is included in the interpretation of the Qur'anas well as its characters, diverse perspectives related to israiliyyat and israiliyyat authentication in the interpretation of the Qur'an. The purpose of this study is to determine the authenticity of the israeliyyat stories in the interpretation of the Qur'an. This research is important considering that the Qu’ran is a book as well as a guide to human life, a manuscript that is protected from forgery and its authenticity is guaranteed by Allah SWT. The existence of the Qur'an is not only read and then memorized, but studied and studied from numerous scientific disciplines by humans throughout the ages, so that if there is an error in the interpretation, the consequences will be fatal. The methodology used in this study is a literary and historical approach. According to the findings of this study, there are three perspectives on  israiliyyat authentication and its application in interpretation, namely: 1) receptionist, 2) rejectionist, 3) creative synthesis. For detailed discussion, the author explains in this article.